2011
DOI: 10.1016/s0028-3843(14)60064-5
|View full text |Cite
|
Sign up to set email alerts
|

Spinal epidural abscess following epidural cannulation for flail chest analgesia: a case report

Abstract: Epidural abscess after epidural catheterization is a rare complication. Neurological manifestations vary and the patient described here presented with complete paraplegia. He was managed by surgical decompression and did well postope-ratively. We present a case report and review of the literature of thoracic epidural abscess following catheterization for epidural analgesia with near total neurological recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It was reported that several causative organisms may cause SEA, including Staphylococcus aureus , Gram-negative bacteria, coagulase-negative bacteria, staphylococcus, Escherichia coli , Pseudomonas aeruginosa , streptococcus species, and Mycobacterium spp. [2,20,21] Among them, S. aureus is the leading agent. [22] Notably, the sensitivity of blood cultural test may decline with pre-use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that several causative organisms may cause SEA, including Staphylococcus aureus , Gram-negative bacteria, coagulase-negative bacteria, staphylococcus, Escherichia coli , Pseudomonas aeruginosa , streptococcus species, and Mycobacterium spp. [2,20,21] Among them, S. aureus is the leading agent. [22] Notably, the sensitivity of blood cultural test may decline with pre-use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] It is much rarer due to the esophageal penetration by a swallowed fishbone, though ingestion of a fishbone is a common cause of esophageal injury. As its low incidence limits many health care practitioners exposure to this pathology, approximately 50% of patients are initially misdiagnosed at the time of presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, ( 16 ) complications of microbial infections during anesthesia must be considered, and meningitis is one of the most important. The literature describes Staphylococcus aureus as the most frequent etiology of complications during neuroaxis regional block.…”
Section: Discussionmentioning
confidence: 99%
“…1 It was not until 1947 that Barrett and Olson made the first attempts at surgical repair of EP. 2,3 Despite update progress in intensive care, diagnostic methods, and endoscopic or surgical therapeutic measures of EP, the general mortality is still about 20%. 4 Diagnostic delays/errors due to frequent atypical clinical presentations/incomplete history, associated with the absence of clear management policies can partly explain this poor prognosis.…”
Section: Introductionmentioning
confidence: 99%